Anti-biofilm Activity of Purified Compounds E1 and E2 Isolated from Streptomyces griseus Against Pathogenic Bacteria - Rajeb, Eslah Shaker (International Journal of Pharmaceutical & Biological Archive, 2022)
Streptomyces griseus is capable of producing novel bioactive compounds, as well as investigating their biological effect on biofilm pre-production by aerobic bacterial isolates from skin wounds and burns when examined. The cultural characteristics the morphology of arial mycelium colors, Pale yellow on ISP2 media at 28°C for 7–14 days and the biochemical tests.